Optimasi konseling behavioral melalui teknik self management untuk mengatasi perilaku membolos - Dewi, Anisha Fitri; Dantes, Nyoman; Lestari, Luh Putu Sri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
This study aims to determine the effect of a behavioral approach with self-management techniques to minimize truancy behavior in class XI students of SMAN 4 Singaraja. The design in this study used "Pre-Experimental Design: One Group Pre Test-Post Test Design", a purposive sampling method involving 10 students and obtained research samples in class XI IPS 1, XI IPS 2, XI IPS 3, XI IPA 1, XI IPA 6, and XI BB 2. The data collection method used was observation and counseling documentation. In data analysis using a list of student attendance. Next, the calculation of the test analysis will be carried out using the Wilcoxon Marked-Level Test calculation. After obtaining the calculated t value, then proceed with consulting the t table value of a significance level of 0.05 of -1.96 or in other words Z0.025 = -1.96. The Z value obtained in the study was 2.26. The Z value in the table with a significance level of 0.05 is -1.96. Or in other words Z0.025 = -1.96. This means Zhit>Za/2, so H0 is rejected, H1 is accepted. So, the application of behavioral counseling using self-management techniques is effective in minimizing truant behavior in class XI students of SMAN 4 Singaraja.